Paradox lost on the U.S.-Mexico border: U.S. Latinas and cesarean rates - Theresa Morris; Amanda Gomez; Miriam Naiman-Sessions; Christine H. Morton (BMC, 2018)
Abstract Background We apply Intersectional Theory to examine how compounded disadvantage affects the odds of women having a cesarean in U.S.-Mexico border hospitals and in non-border hospitals. We define U.S. Latinas with compounded disadvantage as those who have neither a college education nor private health insurance. Results Analyzing quantitative and qualitative data from Childbirth Connection's Listening to Mothers III Survey, we find that, consistent with the notion of the Latinx Health Paradox, compounded disadvantage serves as a protective buffer and decreases the odds of cesarean among women in non-border hospitals. However, the Latinx Health Paradox is absent on the border. Conclusion Our data show that women with compounded disadvantage who give birth on the border have significantly higher odds of a cesarean compared to women without such disadvantage. Further, women with compounded disadvantage who give birth in border hospitals report receiving insufficient prenatal, pregnancy, and postpartum information, providing a direction for future research to explain the border disparity in cesareans.